Challenges and Opportunities in Transforming Rural Governance Through E-Government in Indonesia: Tantangan dan Peluang dalam Mentransformasi Tata Kelola Pemerintahan Pedesaan Melalui E-Government di Indonesia - Amiril, Nur; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2024)
General Background: The adoption of E-Government systems is increasingly important in improving public services, particularly at the local government level, to enhance transparency and accessibility. Specific Background: In Indonesia, Village Information Systems (SID) have been introduced to streamline communication, resource management, and service delivery in rural areas. Sugihwaras Village in Sidoarjo Regency is one such location where SID has been implemented. Knowledge Gap: Despite its potential, the effectiveness of SID implementation remains underexplored, particularly in terms of communication, resources, and its impact on rural governance. Aims: This study aims to analyze and describe the implementation of E-Government through SID in Sugihwaras Village, focusing on the four indicators: communication, resources, disposition, and bureaucratic structure, using Edward III's policy implementation model. Results: The findings indicate that communication and resource allocation are the primary issues hindering SID effectiveness. Inadequate operator training and a lack of budget for operator fees have led to outdated information and diminished motivation. However, strong commitment from local government and adherence to standard operating procedures (SOPs) have ensured that the system continues to function. Novelty: This study highlights the crucial role of consistent training and budgetary support in enhancing E-Government systems at the village level, particularly in rural Indonesia. Implications: Strengthening operator skills and ensuring adequate financial support are essential for optimizing SID as a tool for public information transparency and service delivery, contributing to improved rural governance and E-Government effectiveness. Highlights: Communication gaps limit the Village Information System's efficiency. Budget constraints reduce operator motivation and system updates. Government commitment keeps the system operational despite obstacles. Keywords: E-Government, Village Information System, rural governance, communication, resource allocation